On the Lagrangian and Hamiltonian aspects of infinite-dimensional dynamical systems and their finite-dimensional reductions - Prykarpatsky, Y.A.; Samoilenko, A.M. (Нелінійні коливання, 2005)
Some aspects of the description of Lagrangian and Hamiltonian formalisms naturally arising from the invariance structure of given nonlinear dynamical systems on the infinite-dimensional functional manifold is presented. The basic ideas used to formulate the canonical symplectic structure are borrowed from the Cartan’s theory of differential systems on the associated jet-manifolds. The symmetry structure reduced on the invariant submanifolds of critical points of some nonlocal Euler – Lagrange functional is described thoroughly for both differential and differential discrete dynamical systems. The Hamiltonian representation for a hierarchy of Lax-type equations on a dual space to the Lie algebra of integraldifferential operators with matrix coefficients, extended by evolutions for eigenfunctions and adjoint eigenfunctions of the corresponding spectral problems, is obtained via some special Backlund transformation. The connection of this hierarchy with integrable by Lax spatially two-dimensional systems is studied.